Mobilizing the trust for Islamic insurance (takaful). Issue 4 (2nd May 2019) - Morrison, Scott
Abstract: Takaful is the Islamic counterpart of indemnity-based insurance. It is a cooperative, charitable scheme comprising a fund compensating participants in case of the occurrence of specified adverse events. The features of takaful distinguishing it from insurance give rise to three legal problems: first, the voluntary, non-contractual donation—counterpart of a premium; secondly, the capacity in which the takaful operator invests and manages the fund; and thirdly, the operator's obligation to return the residue of the fund to participants at scheme expiry. This article explores how the introduction of the English trust provides an amenable solution to these three problems.